TINGKAT PARTISIPASI SISWA SEKOLAH MENENGAH PERTAMA DALAM PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Christina Purbawati; Laili Etika Rahmawati; Lathifah Nurul Hidayah; Lupita Sari Pitra Wardani (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
This study aims to identify the level of students participation in virtual learning during the Covid-19 pandemic. The research location is SMP Negeri 1 Kalijambe with the subjects of class VIII students. The study was conducted in March to May 2020. Data collection techniques in this study through interviews. The research data are in the form of learning outcomes of Grade VIII students online based on the co-19 pandemic era. The results obtained from this study indicate the level of students participation in virtual learning during the Covid-19 pandemic by implementing online learning through WhatsApp is relatively high. This can be seen from the results of class VIII participation which has an average score of 5.2. There are five forms of online learning participation including student attendance, discipline in doing assignments, cooperation in doing group assignments, polite speaking, implementing midterm and final exam.